Explainable extreme boosting model for breast cancer diagnosis - Tsehay Admassu Assegie; Sangeetha Ganesan; Ravulapalli Lakshmi Tulasi; Radha Mothukuri; Ayodeji Olalekan Salau; Tamilarasi Suresh (Institute of Advanced Engineering and Science, 2023)
This study investigates the Shapley additive explanation (SHAP) of the extreme boosting (XGBoost) model for breast cancer diagnosis. The study employed Wisconsin’s breast cancer dataset, characterized by 30 features extracted from an image of a breast cell. SHAP module generated different explainer values representing the impact of a breast cancer feature on breast cancer diagnosis. The experiment computed SHAP values of 569 samples of the breast cancer dataset. The SHAP explanation indicates perimeter and concave points have the highest impact on breast cancer diagnosis. SHAP explains the XGB model diagnosis outcome showing the features affecting the XGBoost model. The developed XGB model achieves an accuracy of 98.42%.